Řízení měnového rizika - Fialová, Ilona; Fialová Ilona (České vysoké učení technické v Praze, 2017)
V první části své bakalářské práce se zaměřuji na definici derivátů, důvody jejich vzniku a možnosti jejich využití. Následuje výčet jednotlivých druhů derivátů a rozdíly mezi nimi. Poté se již soustředím na měnové deriváty, jejich použití a výpočet jejich reálné hodnoty. Praktická část začíná zhodnocením spolupráce společností s Unicreditbank Czech Republic and Slovakia, a.s. při uzavírání derivátových obchodů. Zhodnocuji výhody a nevýhody jednotlivých typů měnových derivátů nabízené touto bankou. V poslední části mé bakalářské práce je analýza využití měnových derivátů společností SEKO Aerospace a.s.

In the first part of my bachelor thesis I focus on the definition of derivates, the reasons for their creation and the possibilities of their use. It is followed by a list of the different types of derivates and the differences between them. Afterwards I focus on currency derivatives, their use and calculation of their real value. The practical part starts with the evaluation of the cooperation of companies with Unicreditbank Czech Republic and Slovakia, a.s. in closing derivative deals. I evaluate the advantages and disadvantages of different types of currency derivatives offered by this bank. The last part of my bachelor thesis is the analysis of the use of currency derivatives by company SEKO Aerospace a.s.
Currency Risk Management
Keywords: Finanční deriváty,futures,forward,swap,opce,měnové riziko; Financial derivatives,futures,forward,swap,option,currency risk